PERBANDINGAN PERBANDINGAN KURIKULUM PENDIDIKAN DI FINLANDIA, MALAYSIA, DAN INDONESIA : SEBUAH ANALISIS KOMPARATIF - Rokayati Rokayati Yati (Edulead : Journal of Education Management, 2023)
Abstract The educational curriculum is one of the important factors in determining the quality of a country's education. This study aims to compare the educational curricula in Finland, Malaysia, and Indonesia, with a focus on the differences, similarities, and success of their implementation. This research method uses a comparative approach by analyzing documents related to educational curricula in the three countries. Data was also collected through a literature review. The results of the study show that there are significant differences in the education curricula in Finland, Malaysia and Indonesia. Finland has a very student-centred approach to education, with a focus on developing life skills and creativity. Malaysia has a curriculum that is more structured and oriented toward mastering certain subjects. Meanwhile, Indonesia has a curriculum that is more focused on mastery of subject matter and preparation for national exams. Even though there are differences in the approach and focus of the curriculum, the three countries have similarities in efforts to improve the quality of education. All countries aim to develop students' life skills, creativity and innovation. In addition, the three countries also recognize the importance of developing student independence in the learning process. The conclusion of this study is that a comparison of educational curricula in Finland, Malaysia, and Indonesia shows significant differences in curriculum approach and focus. Finland has a very student-centred approach, while Malaysia and Indonesia focus more on mastering subject matter. Nonetheless, these three countries have similarities in efforts to improve the quality of education and develop students' life skills. This research provides valuable insights for the development of educational curricula in Indonesia, taking into account the successes and weaknesses of other countries.